THE IMPACT OF ARTIFICIAL INTELLIGENCE ON ORGANIZATIONAL CULTURE: A PATHWAY TO DIGITAL TRANSFORMATION - Pawar, Priyanka; Shah, Aditee Huparikar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In the rapidly evolving business landscape, Artificial Intelligence (AI) has emerged as a pivotal driver of digital transformation, fundamentally reshaping organizational culture. This study explores the multifaceted impact of AI on organizational culture and assesses managers’ perceptions of AI-facilitated digital transformation. Employing a quantitative research design, data were collected from 244 managers across various industries, including the IT sector, where AI has significantly influenced operational and strategic practices. The research tested two primary hypotheses: H1, which posits that AI has a significant impact on organizational culture, and H2, which asserts that managers hold a positive perception of digital transformation through AI. Utilizing one-sample t-tests, the findings robustly supported both hypotheses. The results indicate that AI integration has substantially altered communication, collaboration, core values, decision-making processes, and fostered a culture of innovation and continuous improvement within organizations. Additionally, managers overwhelmingly perceive AI as a critical enabler of digital transformation, enhancing overall performance, driving sustainable growth, improving customer satisfaction, and aligning with strategic objectives. These outcomes underscore the essential role of managerial support and strategic alignment in successfully leveraging AI for cultural and digital advancements. The study contributes to the existing literature by providing empirical evidence on the interconnectedness of AI, organizational culture, and digital transformation, while highlighting the need for further research into sector-specific impacts and longitudinal effects. Practical implications suggest that organizations should cultivate supportive environments and align AI initiatives with cultural and strategic goals to maximize the benefits of digital transformation.